Studies on antidiabetic and antioxidant effects of local tualang Oney in streptozotocin-induced diabetic rats - Wahab, Mohd Suhaimi Ab (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
This study shows that tualang honey does not produce antioxidant effect in non-diabetic rats. neither does tt increase or decrease blood glucose in normal/healthy rats. Our results also show that tualang honey. in a dose dependent response, ameliorates oxidative stress in kidney of diabetic rats and also has hypoglycemic effect. Tualang honey produces weight gain more than glibenclamide and/or metformin in experimental diabetes.